Hygienic Conditions of Learning as a Factor in Preserving the Health of School-Age Children - Usmanova , Madina; Maxmudova , Odinaxon (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the influence of hygienic learning conditions on the health of school-age children. Particular attention is paid to the analysis of such important factors as classroom lighting, indoor microclimate, temperature conditions, air quality, educational workload, daily routine, and the sanitary-hygienic state of school premises. Proper organization of the educational environment plays a significant role in preventing fatigue, reducing stress, and supporting students’ physical and mental well-being. The study also highlights the importance of regular ventilation, comfortable furniture, cleanliness of classrooms, and compliance with safety standards. It is concluded that adherence to hygienic requirements and the creation of favorable learning conditions are essential factors for preserving, strengthening, and improving the health of pupils, as well as increasing their academic performance and overall development